2022
DOI: 10.3390/w14132028
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Activated Chlorine Dioxide Oxidation for Micropollutant Abatement: A Review on Kinetics, Reactive Sites, and Degradation Pathway

Abstract: Recently, ClO2-based oxidation has attracted increasing attention to micropollutant abatement, due to high oxidation potential, low disinfection byproduct (DBPs) formation, and easy technical implementation. However, the kinetics, reactive sites, activation methods, and degradation pathways involved are not fully understood. Therefore, we reviewed current literature on ClO2-based oxidation in micropollutant abatement. In direct ClO2 oxidation, the reactions of micropollutants with ClO2 followed second-order re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…These are all oxidations that have previously been reported in aerobic environments. 67 However, to the best of our knowledge, this is the first report of transformation products for diphenhydramine (monohydroxylation and ether dealkylation) in a CAS system. Fig.…”
Section: Resultsmentioning
confidence: 81%
“…These are all oxidations that have previously been reported in aerobic environments. 67 However, to the best of our knowledge, this is the first report of transformation products for diphenhydramine (monohydroxylation and ether dealkylation) in a CAS system. Fig.…”
Section: Resultsmentioning
confidence: 81%
“…It was shown that by application of ClO 2 pre-oxidation the chloroform formation could be reduced, although more chloral hydrate formation occurred. Recently, Ma et al (2022) published a review on degradation pathways when ClO 2 was applied to micropollutants.…”
Section: B3 Chlorine Dioxidementioning
confidence: 99%
“…Recently, Ma et al. ( 2022 ) published a review on degradation pathways when ClO 2 was applied to micropollutants.…”
Section: Appendix B – Literature Overview Of the Formation Of Tp Duri...mentioning
confidence: 99%